PENGARUH PENDAMPINGAN TERHADAP PENURUNAN KADAR GLUKOSA DARAH PASIEN DIABETES MELLITUS TIPE II - Michran Marsaoly; Khartini Kaluku (Poltekkes Kemenkes Maluku, 2017)
About 90-95% of the incidence of diabetes worldwide is type II diabetes. Education is the main basisof treatment and prevention of perfect DM. This study aimed to determine the effect of mentoringprogram on knowledge, dietary compliance, medication adherence, physical activity and blood sugarlevels of type 2 DM patients in the Air Besar Health Center of Ambon City. Type of this research ispure experiment. In this design, grouping of sample members is done randomly. Mentoring program iscarried out before and after the intervention. This research was conducted at the Air Besar HealthCenter, from August to September 2015. The results showed that there were differences in knowledgebetween before and after mentoring program of type 2 DM patients with p value <0.05, there was aneffect of mentoring on diet compliance and blood glucose levels with p value <0.05. It is expected to beone of the information for health agencies, especially the Air Besar Health Center in order to improveservices to type 2 DM patients in an effort to increase metabolic control and as input for the MalukuProvincial Government, especially the Health Office in developing educational intervention programswith a mentoring approach in achieving better metabolic control.